2006
DOI: 10.1108/14635770610644565
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of supply chain performance measurement in the Indian automotive sector

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 40 publications
2
114
0
Order By: Relevance
“…As Lakhal et al (2006) indicate that organizations with TQM systems in place coherently surpass the industry criterion for return on investment. While, Saad and Patel (2006) reasoned that by enforcing TQM, the companies acquired in-depth discernment of the key element related with the quality supply chain function practices in Indian automotive industries. They also proved that TQM in supply chain is significant to ameliorate key elements such as quality, delivery and lead-time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Lakhal et al (2006) indicate that organizations with TQM systems in place coherently surpass the industry criterion for return on investment. While, Saad and Patel (2006) reasoned that by enforcing TQM, the companies acquired in-depth discernment of the key element related with the quality supply chain function practices in Indian automotive industries. They also proved that TQM in supply chain is significant to ameliorate key elements such as quality, delivery and lead-time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The same experience also faces locally-owned firms in other developing countries. According to Saad and Patel (2006), despite a high level of tariffs imposed on imported components, Indian or local suppliers still have a limited level of technological capability, poor product quality and lack of reliability on parts delivery.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Commencing from the late 1980s onwards, less tangible and non-financial measures have been extensively employed in tandem with the advent of new management systems, such as supply chain management (SCM), justin-time delivery (JIT), and total quality management (TQM). Intangible measures include communication, learning, trust (Saad and Patel, 2006), stakeholder satisfaction, competitive position (Garrigos-Simon et al, 2005), quality of product, and throughput rate (Abu Kasim et al, 1989).…”
Section: Determinants Of Firm Performancementioning
confidence: 99%
“…From a survey conducted by BusinessLine (http://www.thehindubusinessline.com), it was found that the Indian automobile industries are viewing towards improving their SCP to maintain a good reputation and stability in the competitive environment. Limited studies, towards improving the SCP of the Indian automobile industry, have been reported (Saad and Patel, 2006). As discussed earlier, CSR is becoming a proactive theme for implementation with supply chain functions of an organisation.…”
Section: Problem Descriptionmentioning
confidence: 99%